Brazilian guidelines for the management of psychomotor agitation: pharmacological approach 1 – rapid tranquilization - Baldaçara, Leonardo (2021)
There is evidence suggesting that pharmacological approach to psychomotor agitation is indicated only when non-pharmacological approaches fail. The cause of agitation, side effects and contraindications of the different medications should guide the choice of the medication in each case. Oral administration is preferred;intravenous administration should be avoided. All patients should be monitored before and after receiving the medication. Systematic review registration: CRD42017054440.